2016
DOI: 10.15405/epsbs.2016.08.24
|View full text |Cite
|
Sign up to set email alerts
|

Flood Disaster Management in Malaysia: A Review of Issues of Flood Disaster Relief during and Post-Disaster

Abstract: This paper describes the issues and problem of disaster relief provided by the government to the victims in Malaysia, during and post-disaster caused by flooding. Presently, the delivery relief system in flood management was predominantly an official strategy based on Directive No. 20 by National Security Council (MKN). These instructions outline a policy on disaster management and has set the role and responsibilities of the agencies involved and also covers the action of monitoring the activities in disaster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…The problems and issues regarding the relief operation during the disaster had been revealed by many researchers. Shafiai (2016) indicated that the government only acted after the disaster occurred and did not foresee in the policy an adequate preparation for the future. It is also uncovered that the assistance provided to the victims was irregular, inadequate and delayed, especially in the aid distribution of food, water and other basic necessities (Karim et al, 2016;Nurumal, Aung, & Yusoff, 2017).…”
Section: Current Issues and Problemsmentioning
confidence: 99%
“…The problems and issues regarding the relief operation during the disaster had been revealed by many researchers. Shafiai (2016) indicated that the government only acted after the disaster occurred and did not foresee in the policy an adequate preparation for the future. It is also uncovered that the assistance provided to the victims was irregular, inadequate and delayed, especially in the aid distribution of food, water and other basic necessities (Karim et al, 2016;Nurumal, Aung, & Yusoff, 2017).…”
Section: Current Issues and Problemsmentioning
confidence: 99%
“…Shafiai & Khalid (2016) argues that during the process of evacuation, victims are expected to receive help from the government officials to reduce the distress condition, this however was denied and have been discussed by other researchers that the assistance provided to victims is slow and irregular with inadequate support (Said, Gapor, Samian, & Abd Malik, 2013). Moreover, the problems were caused by insufficient relief operation and dissatisfaction with the management of the evacuation centre.…”
Section: Problems and Issuesmentioning
confidence: 99%
“…Series: Materials Science and Engineering 291 (2017) 012023 doi:10.1088/1757-899X/291/1/012023 as earthquakes, volcano, and typhoon because lies in a geologically stable region just outsides the "Pacific Ring of Fire" [1]- [5]. Hence, it is free from earthquakes and volcanic eruptions.…”
mentioning
confidence: 99%
“…However, that does not mean Malaysia is totally free from natural disasters and calamities, as it is often hit by floods, droughts, landslides, haze, tsunamis, and human made disasters [4]. The most intense natural disaster experienced in Malaysia is the flood [1], [2], [4], [5]. The Malaysia flood that happened from 15 December 2014 -3 January 2015, has been described as the worst floods in decades.…”
mentioning
confidence: 99%
See 1 more Smart Citation